Goldratt and the theory of constraints. the quantum leap in management. - Techt, Uwe. ([Place of publication not identified] : Ibidem-Verlag.)
Businessmen and managers, consultancy clients, readers of the Goldratt novels, and workshop attendees often ask: What is this Theory of Constraints' How can it benefit me' How is it different from other management theories' Is there something I can read to quickly understand its fundamentals' This book is an answer to these questions. Using engaging language and offering many real-life examples, it provides an overview of the methods and tools of the Theory of Constraints: Drum-Buffer-Rope, Buffer Management, Throughput Accounting, Pull Distribution, Irresistible Offer, Corporate Strategy, and Viable Vision. You will learn how to recognize and use constraints, how to complete projects quickly and reliably, and how to gain a competitive lead and to turn it into profit.
Treatment planCarrying out the treatment; The methods of effective thinking; What needs to be changed?; Tool 1: The Conflict Cloud; Tool 2: The Current Reality Tree; Where should the change lead?; Tool 3: Resolving the conflict; Tool 4: The Future Reality Tree; How do we bring about these changes?; Tool 5: The Prerequisite Tree; Tool 6: Transition tree; Food for thought; Our stock levels are too high ... and often too low!; Dilemma: Large warehouse or small warehouse?; What is distribution?; Constraint: The client willing to buy; Using the constraint; How high do stock levels need to be?
eBooks on EBSCOhost
Keywords: Business; Affaires; businesses (business enterprises); business (commercial function); BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; Business